2017
DOI: 10.1093/cvr/cvx069
|View full text |Cite
|
Sign up to set email alerts
|

New thrombolytic strategy providing neuroprotection in experimental ischemic stroke: MMP10 alone or in combination with tissue-type plasminogen activator

Abstract: These results show that MMP10, either alone or in combination with tPA, might represent a new strategy for thrombolysis in ischemic stroke, providing higher protection against cerebrovascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Broad-spectrum MMP inhibitor-tPA combination has also showed protective effects in reducing IV tPA-related hemorrhagic complication [121]. Very interestingly, besides MMP inhibitor, combination of MMP-10 plus tPA exhibited effects of BBB protection, neuronal excitotoxicity reduction, and calcium overload mitigation [122]. Molecules targeting coagulation pathway have also been included as a potential adjunct of IV tPA therapy.…”
Section: Combination Therapy For IV Tpa Thrombolysismentioning
confidence: 99%
“…Broad-spectrum MMP inhibitor-tPA combination has also showed protective effects in reducing IV tPA-related hemorrhagic complication [121]. Very interestingly, besides MMP inhibitor, combination of MMP-10 plus tPA exhibited effects of BBB protection, neuronal excitotoxicity reduction, and calcium overload mitigation [122]. Molecules targeting coagulation pathway have also been included as a potential adjunct of IV tPA therapy.…”
Section: Combination Therapy For IV Tpa Thrombolysismentioning
confidence: 99%
“…In the same thromboembolic stroke model, administration of MMP-10 in combination with tissue-type plasminogen activator (tPA) significantly reduced the infarct size as compared with tPA alone. 14 In contrast to animal studies, increased MMP-10 protein levels were reported in human ischaemic brain. 8 …”
Section: Discussionmentioning
confidence: 85%
“…In addition, MMPs may play a role in thrombolysis, since the fibrinolytic system and MMPs cooperate in thrombus dissolution by directly targeting fibrin(ogen) or by collaborating with plasmin 20,21 . Specifically, our group described the fibrinolytic role of MMP-10 by preventing the activation of thrombin-activatable fibrinolysis inhibitor (TAFI) 22 in experimental models of stroke 23,24 . Based on these results, we developed a potent MMPs inhibitor, CM-352, which inhibits MMP-10 and MMP-3 and fibrinolysis 25 , and effectively reduces bleeding, hematoma expansion, and functional impairment in different experimental models of haemorrhage with no signs of thrombotic side effects 26,27 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%